THE LIFTING OF THE SECRET OF COMMUNICATIONS AND THE EXCESSIVE DELAY IN THE DELIVERY OF INFORMATION BY THE TELEPHONE COMPANIES - Montero León, Susy (2023)
Given the constant increase in the crimes of femicide and hired assassination in the districts of Ate and Santa Anita, the Public Ministry has as a fundamental tool the restrictive measure of rights of the Lifting of the Secret of Communications, to know the identity of the material author and arrive at the clarification of the facts; however, the reports of the telephone companies are sent in a very long period of eight to fourteen months after being requested, which leads to serious delay and damage to the investigation due to the excessive delay in the delivery of the information. information, since, given the expiration of the procedural deadlines and the lack of identification of the perpetrator of the act, the prosecutor proceeds to make the unfair decision to file the investigation and the death of the victim remains unpunished, therefore, It is necessary to establish a time limit of 90 calendar days for the delivery of the required information, under the criminal responsibility of the officials in charge and imposing the sanction with a fine on the telephone companies.